1992
DOI: 10.1111/j.1600-051x.1992.tb01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Location of the mucogingival junction 18 years after apically repositioned flap surgery

Abstract: The apically repositioned flap procedure, by definition, implies that the mucogingival junction (MGJ) is shifted into an apical location. That this actually would be the case has never been shown in long-term studies. The 13 subjects in the present study had during the years 1964-1965 received treatment of moderately advanced periodontal disease (probing pocket depths less than or equal to 5 mm) in the lower jaw. An apically repositioned flap (ARF) procedure was applied in the left or right half of the mandibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
55
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 10 publications
9
55
0
2
Order By: Relevance
“…27,28 and 2) the tendency of the MGJ to regain its "genetically" defined position following its coronal "dislocation" with the CRF procedure used to achieve root coverage. Support for the concept that the MGJ will, over time, regain its original position is evident in a study by Ainamo et al, 3 who reported that the apically repositioned procedure did not result in a permanent apical shift. The mechanism of tissue specificity appears to rest within the connective tissue; that is, tissue from alveolar mucosa forms a non-keratinized epithelium, whereas that from gingival connective tissue and the periodontal ligament forms a keratinized gingival epithelium.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…27,28 and 2) the tendency of the MGJ to regain its "genetically" defined position following its coronal "dislocation" with the CRF procedure used to achieve root coverage. Support for the concept that the MGJ will, over time, regain its original position is evident in a study by Ainamo et al, 3 who reported that the apically repositioned procedure did not result in a permanent apical shift. The mechanism of tissue specificity appears to rest within the connective tissue; that is, tissue from alveolar mucosa forms a non-keratinized epithelium, whereas that from gingival connective tissue and the periodontal ligament forms a keratinized gingival epithelium.…”
Section: Discussionmentioning
confidence: 91%
“…Ainamo et al 3 explored the position of the MGJ 18 years after contralateral gingivectomies and apically repositioned flap procedures and observed no differences in the width of gingival tissues, but a shift in the position of the MGJ to its original position. This observation was partly attributed to the hypothesis that muscular attachments that are surgically displaced apical to the MGJ revert back to their original location.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[15] This MGJ has tendency to reestablish itself to the original position leading to gain in KTW. [2223]…”
Section: Discussionmentioning
confidence: 99%
“…The second part, related to patient satisfaction with the esthetic consequence evaluated at the 6-months follow-up visit based on a VAS (VAS-E). [1015]…”
Section: Methodsmentioning
confidence: 99%